Natural Sesquiterpene Lactones Enhance Chemosensitivity of Tumor Cells through Redox Regulation of STAT3 Signaling - Butturini, Elena (Oxid Med Cell Longev, 2019)
STAT3 is a nuclear transcription factor that regulates genes involved in cell cycle, cell survival, and immune response. Although STAT3 activation drives cells to physiological response, its deregulation is often associated with the development and progression of many solid and hematological tumors as well as with drug resistance. STAT3 is a redox-sensitive protein, and its activation state is related to intracellular GSH levels. Under oxidative conditions, STAT3 activity is regulated by S-glutathionylation, a reversible posttranslational modification of cysteine residues. Compounds able to suppress STAT3 activation and, on the other hand, to modulate intracellular redox homeostasis may potentially improve cancer treatment outcome. Nowadays, about 35% of commercial drugs are natural compounds that derive from plant extracts used in phytotherapy and traditional medicine. Sesquiterpene lactones are an interesting chemical group of plant-derived compounds often employed in traditional medicine against inflammation and cancer. This review focuses on sesquiterpene lactones able to downmodulate STAT3 signaling leading to an antitumor effect and correlates the anti-STAT3 activity with their ability to decrease GSH levels in cancer cells. These properties make them lead compounds for the development of a new therapeutic strategy for cancer treatment.